SAR131675 Receptor Tyrosine Kinase Inhibitor Induces Apoptosis through Bcl- 2/Bax/Cyto c Mitochondrial Pathway in Human Umbilical Vein Endothelial Cells - Babaei, Zeinab; Panjehpour, Mojtaba; Parsian, Hadi; Aghaei, Mahmoud (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Background: Tyrosine Kinase Inhibitors (TKIs) can be used to inhibit cancer cell proliferation by targeting the vascular endothelial growth factor receptor (VEGFR) family. SAR131675 is a highly selective receptor tyrosine kinase inhibitor to VEGFR3 that reveals the inhibitory effect on proliferation in human lymphatic endothelial cells. However, the molecular mechanisms underlying this process are generally unclear. Objective: This study was performed to investigate the possible involvement of the Bcl-2/Bax/Cyto c apoptosis pathway in Human Umbilical Vein Endothelial Cells (HUVECs). In addition, the role of Reactive Oxygen Species (ROS) and mitochondrial membrane potential was evaluated. Methods: The effect of SAR131675 on HUVEC cell viability was evaluated by MTT assay. The activity of SAR131675 in inducing apoptosis was carried out through the detection of Annexin V-FITC/PI signal by flow cytometry. To determine the mechanisms underlying SAR131675 induced apoptosis, the mitochondrial membrane potential, ROS generation, the activity of caspase-3, and expression of apoptosis-related proteins such as Bcl-2, Bax, and cytochrome c were evaluated in HUVECs. Results: SAR131675 significantly inhibited cell viability and induced apoptosis in HUVECs in a dose-dependent manner. Moreover, SAR131675 induced mitochondrial dysfunction, ROS generation, Bcl-2 down-regulation, Bax upregulation, cytochrome c release, and caspase-3 activation, which displays features of mitochondria-dependent apoptosis signaling pathway. Conclusion: Our present data demonstrated that SAR131675-induced cytotoxicity in HUVECs associated with the mitochondria apoptotic pathway. These results suggest that further studies are required to fully elucidate the role of TKIs in these cellular processes.
Keywords: mitochondrial pathway